IMPORTANCE OF HEALTHY NUTRITION IN LIVER DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Nutrition plays a critical role in the management and prevention of liver diseases. Adequate intake of macronutrients and micronutrients supports liver function, enhances immune response, and helps in tissue regeneration. Malnutrition or improper dietary habits can exacerbate liver injury, promote inflammation, and accelerate disease progression. This article emphasizes the significance of individualized dietary strategies in patients with liver disorders to improve clinical outcomes and overall quality of life.